COVID-19 and Political Preferences through Stages of the Pandemic: The Case of the Czech Republic - Alena Bičáková; Štepán Jurajda (Institute of Labor Economics (IZA), 2024)
We track the effects of the COVID-19 pandemic on political preferences through 'high' and 'low' phases of the pandemic. We ask about the effects of the health and the economic costs of the pandemic measured at both personal and municipality levels. Consistent with the literature, we estimate effects suggestive of political accountability of leaders during 'high' pandemic phases. However, we also find that the pandemic political accountability effects are mostly short-lived, and do not extend to the first post-pandemic elections.
Keywords: D72; 330; COVID-19; political accountability